α-Amylase Changed the Catalytic Behaviors of Amyloglucosidase Regarding Starch Digestion Both in the Absence and Presence of Tannic Acid - Li, Shuangshuang; Wu, Wenjing; Li, Jing; Zhu, Shengnan; Yang, Xi; Sun, Lijun (Frontiers in Nutrition, 2022)
The courses of starch digestion with individual α-amylase (AA), amyloglucosidase (AMG) and AA/AMG bi-enzyme system were performed and analyzed by 1st-order-reaction equations in the absence and presence of tannic acid (TA). An antagonistic effect between AA and AMG occurred at the digestion phase of readily-digestible-starch due to the higher catalytic efficiency of AMG for starchy-substrates with more complex structures. This effect caused a faster rate of glucose production with AMG than with AA/AMG bi-enzyme system at this phase both in the absence and presence of TA. TA had a higher binding affinity to AA than to AMG as accessed by several methods including inhibition kinetics, fluorescence quenching, isothermal titration calorimetry and molecular docking. Besides, differential scanning calorimetry indicated that the change in thermal and structural stabilities of the enzymes in the presence of TA was related to the enzyme residues involved in binding with TA, rather than the inhibitory effects of TA. The binding characters of TA to both enzymes resulted in more ‘free’ AMG without TA binding in AA/AMG bi-enzyme system than that in individual AMG. This binding property caused more and faster rate of glucose production at the digestion phase of slowly-digestible-starch in the bi-enzyme system.